Elizabeth Todd Edwards correspondence - Edwards, Elizabeth Todd, 1813-1888.
Letters written by Edwards primarily from Andover, Mass., to her daughter and son-in-law, Julia Cook Edwards Baker and Edward Lewis Baker, in Springfield, Ill., relating chiefly to family affairs. The letters include references to Edwards's sister, Mary Todd Lincoln; Harriet Beecher Stowe; Abraham Lincoln's presidential nomination; and Edwards's trip to Washington, D.C., for Lincoln's inauguration.
Sister of Mary Todd Lincoln. Married Ninian Wirt Edwards, 1832.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Baker, Edward Lewis, -- 1829-1897 -- Correspondence; Baker, Julia Cook Edwards, -- 1837-1908 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Inauguration; Lincoln, Mary Todd, -- 1818-1882.; Stowe, Harriet Beecher, -- 1811-1896.; Presidents -- United States -- Election -- 1860.; Andover (Mass.) -- Social life and customs; Springfield (Ill.) -- Social life and customs